The role of using a special support surface in heel pressure ulcers appearance in intensive care unit patients - Karabekiou, Eirini; Kadda, Olga; Marvaki, Christina; Routsi, Christina (Health & Research Journal, 2018)
Introduction: Intensive Care Unit (ICU) patients suffer complications such as the development of pressure ulcers. Aim: The purpose of this study was to investigate the relationship between the use of special designed heel protector and the frequency and severity of heel pressure ulcers occurrence in ICU patients. Material and Method: The studied sample consisted of 40 patients hospitalized in ICU of a general hospital in Attica. Hospital Acquired Skin Injury (HASI) and Cubin Jackson (Score Cubin-Jackson) were used and data analysis was performed by the statistical package SPSS 19. Results: 62,5% of the studied sample were men, with mean age 59±17.7 years and length of hospital stay 21.4±18 days. The preventive intervention applied in the present study was effective, as no patient develop pressure ulcers. However, the incidence of tissue lesions at the unstressed edge did not appear to be influenced by factors such as patient age (p = 0.586), gender (p = 0.674 F = 0.180), total blood protein levels (p = 0.732 ), albumin levels (0.185) and hematocrit (p = 0.669). Conclusions: In those patients that the pressure ulcers heel protectors were applied no one develops pressure ulcers during their stay in ICU. On the contrary, in those patients